Stress hyperglycemia ratio as a mortality predictor in non-diabetic septic patients: a retrospective cohort analysis - Feng, Siyu; Zou, Rui; Wang, Yue; Huang, Yuqin; Zhou, Quan; Huang, Qiang; Xu, Huaqiang (BMC infectious diseases, 2025)
The stress hyperglycemia ratio (SHR) is associated with adverse events in critically ill patients. However, the relationship between SHR and mortality in non-diabetic septic patients remains unclear. This study aimed to investigate the correlation between SHR and mortality in non-diabetic septic patients. This retrospective cohort study utilized data from the Medical Information Mart for Intensive Care (MIMIC-IV) database at Beth Israel Deaconess Medical Center in Boston. The study population was stratified into four groups based on quartiles of the SHR. The primary outcome was in-hospital mortality, while the secondary outcome was ICU mortality. Kaplan-Meier curves, the Log-rank test, and Cox regression analysis were employed to assess the association between SHR and all-cause mortality. Restricted cubic splines (RCS) regression analysis was conducted to explore the nonlinear relationship between SHR and outcomes. Additionally, subgroup analyses were performed to investigate differences among various patient subgroups. This study included a cohort of 1,200 patients, with a median age of 68.44 years, and 43.42% were female. The in-hospital mortality and Intensive Care Unit (ICU) mortality rates were 19.67% and 15.42%, respectively. Cox regression analysis revealed that an elevated SHR was independently associated with both in-hospital mortality (Hazard Ratio [HR], 1.50; 95% Confidence Interval [CI], 1.05-2.13; P = 0.02) and ICU mortality (HR, 1.53; 95% CI, 1.04-2.24; P = 0.03). Furthermore, the relationship between SHR and mortality exhibited a U-shaped pattern, indicating that an increase in SHR correlates with an elevated risk of adverse events. The results of subgroup analyses were generally consistent with these findings. In non-diabetic critically ill septic patients, SHR is significantly associated with an increased risk of adverse events. Consequently, SHR emerges as a potential predictor of poor outcomes in non-diabetic septic patients admitted to the ICU.